Experimental investigation of mechanical properties of UV-Curable 3D printing materials. (6th June 2018) - Hong, Sung Yong; Kim, Ye Chan; Wang, Mei; Kim, Hyung-Ick; Byun, Do-Young; Nam, Jae-Do; Chou, Tsu-Wei; Ajayan, Pulickel M.; Ci, Lijie; Suhr, Jonghwan
Abstract: More recently, three dimensional printing (3D Printing), also known as an additive manufacturing (AM), has been highlighted since it shows a great promise to realize almost any three dimensional parts or structures with computer aided design (CAD). Several different processes are available for 3D printing, which includes fused deposition modeling, selective laser sintering, stereolithography, photopolymerization, and etc. In particular, considerable attention is paid to the 3D printing technique with photopolymerization due to their high resolutions. Unfortunately, the 3D printed products with photopolymerization however possess poor mechanical properties. Understanding of this should be necessary for the advantages of the 3D printing to be fully realized. Here, this study experimentally investigates the mechanical properties of the 3D printed photopolymer through thermomechanical analysis and tensile testing. In this study, it is found that the printed specimens are not fully cured after the 3D printing with photopolymerization. DiBenedetto equation is employed to better understand the relationship between the curing status and tensile properties. In addition to the poor mechanical properties, anisotropic and size dependent tensile properties of the 3D printed photopolymers are also observed. Electron beam treatment is used to ensure the cure of the 3D printed photopolymer and the corresponding tensile properties are characterized and investigated. Graphical abstract: Image 1 Highlights: The interesting mechanical behaviors of 3D printed photopolymer were investigated. Anisotropic and size dependent tensile properties are studied by thermal analysis. Modeling with DiBenedetto equation was employed to understand curing degree. Electron beam treatment was chosen to ensure full cure of 3D printed photopolymer.